The Impact Lowcost Management Balance Exercise Program Reduce Fall Risk In The Elderly In Surakarta - Mutnawasitoh , Asita Rohmah; Mirawati, Dita; Cahyaningrum, Hapsari (Universitas Muhammadiyah Surakarta, 2025)
Introduction: The aging process is a process of aging in the elderly group characterized by, among other things, changes in body balance that will impact the risk of falling. This study aims to determine the effect of the Low-Cost Management Balance Exercise Program as an effort to reduce the risk of falls among the elderly in Surakarta. Method: The type of this research is quantitative with a quasi-experimental design. This study uses a Pre-Test Post-Test with Control Group Design research design with subject selection using purposive sampling. Results: data were analyzed using the paired sample t-test. Results: The result obtained a p-value of 0.001 (p < 0.05), which means that there is a significant difference in balance values before and after the exercise was given in group 1, which is the treatment group. In the control group, a p-value of 0.004 (p < 0.05) was obtained, indicating a significant difference in balance values before and after the exercise was given. Conclusion: The Low-Cost Management Balance Exercise program is effective in reducing the risk of falls in the elderly.